Experimental studies of immunologically mediated enteropathy. III. Severe and progressive enteropathy during a graft-versus-host reaction in athymic mice. - Mowat, A M (1987)
The graft-versus-host reaction (GvHR) in unirradiated (CBA X BALB/c)F1 mice normally produces a proliferative enteropathy consisting of crypt hyperplasia and increased numbers of intraepithelial lymphocytes (IEL), but villus atrophy does not occur. Host T lymphocytes can protect animals from the consequences of a GvHR and, in this study, it is shown that athymic (CBA X BALB/c)F1 mice suffer a more severe systemic GvHR than intact hosts, with the unusual feature of specific anti-host cytotoxic T-lymphocyte (CTL) activity. In addition, nude mice not only had more intense crypt hyperplasia in the small intestine, but also had significant villus atrophy. It is concluded that host T cells normally prevent the progression of GvHR in unirradiated animals, and suggested that villus atrophy reflects a more severe form of the delayed-type hypersensitivity (DTH) reaction, the effects of which are normally limited to crypt hyperplasia.